Biodegradation of Isoprenoids, Steranes, Terpanes, and Phenanthrenes During In Situ Bioremediation of Petroleum‐Contaminated Groundwater. Issue 2 (23rd January 2017) - Beškoski, Vladimir P.; Miletić, Srdjan; Ilić, Mila; Gojgić‐Cvijović, Gordana; Papić, Petar; Marić, Nenad; Šolević‐Knudsen, Tatjana; Jovančićević, Branimir S.; Nakano, Takeshi; Vrvić, Miroslav M.
Abstract : The objective of this study was to stimulate microbial biodegradation of petroleum pollution in groundwater and to analyze changes in the abundance and distribution of organic compounds detectable in petroleum. Bioremediation was conducted in a closed bipolar system, by bioaugmentation with consortia of hydrocarbon degrading microorganisms (HD) and biostimulation with nutrients. Comprehensive two‐dimensional gas chromatography–mass spectrometry (GC × GC–MS) was used to visualize all fractions simultaneously. During the study, the content of total petroleum hydrocarbon (TPH) in groundwater decreased by 92.7% of the initial level, and the average rate of biodegradation was 0.1 mg/L per day. Increased numbers of HD were observed and the dominant genera were Pseudomonas, Rhodococcus, Achromobacter, Bacillus, and Micromonospora . In the first 30 days of bioremediation, there was no significant biodegradation of n ‐alkanes and petroleum biomarkers – isoprenoids such as pristane and phytane, and polycyclic‐saturated hydrocarbons such as terpanes and steranes. However, after 60 days of bioremediation, more than 95% of n ‐alkanes, terpanes and steranes were biodegraded. Phenanthrene and its methyl‐, dimethyl‐, and trimethyl‐isomers were biodegraded and reduced by more than 99% of their initial levels. However, their decomposition had clearly commenced after just 30 days. This is a somewhat surprising result since it follows that the phenanthrenes were more susceptible to biodegradation than the n ‐alkanes and isoprenoids. Depending on the microbial community used for bioaugmentation, biodegradation of phenanthrene can precede biodegradation of saturated hydrocarbons. Abstract : Changes in the abundance and distribution of n ‐alkanes and petroleum biomarkers are followed after stimulation of microbial biodegradation of petroleum pollutant in groundwater. After 60 days of bioremediation, >95% of n ‐alkanes and petroleum biomarkers are biodegraded. Decomposition of unsaturated hydrocarbons such as phenanthrene had clearly commenced after just 30 days which suggest that depending on the microbial community, biodegradation of phenanthrene can precede biodegradation of saturated hydrocarbons.